Caloric restriction coupled with radiation decreases metastatic burden in triple negative breast cancer. Issue 17 (1st September 2016) - Simone, Brittany A.; Dan, Tu; Palagani, Ajay; Jin, Lianjin; Han, Sunny Y.; Wright, Christopher; Savage, Jason E.; Gitman, Robert; Lim, Meng Kieng; Palazzo, Juan; Mehta, Minesh P.; Simone, Nicole L.
ABSTRACT: Purpose : Metastatic breast cancer is devastating and triple negative breast cancers (TNBC) have a higher propensity for metastasis. Improved local control upfront in this aggressive cancer could potentially decrease its propensity toward metastasis. We sought to determine if using caloric restriction (CR) as a systemic therapy, combined with radiation therapy (IR) to the primary tumor, may impact metastatic disease. Methods : An orthotopic mouse model using a highly metastatic, luciferase-tagged TNBC cell line (4T1), was used to generate palpable tumors. Mice were then treated with CR, IR, and a combination of the two. In vivo imaging was performed for metastatic evaluation. Molecular evaluation of the tumors was performed, generating a mechanistic hypothesis for CR, which was then tested with pertinent pathway inhibition in the model. Results : CR significantly increased the time to developing metastases, decreased the overall number and volume of lung metastases, and increased survival. CR decreased proliferation, increased apoptosis and globally downregulated the IGF-1R signaling pathway. Adding an IGF-1R/INSR inhibitor to local IR in vivo accomplished a decrease in metastases similar to CR plus IR, demonstrating the importance of the IGF-1R signaling pathway, and underscoring it as a possible mechanism for CR. Conclusions : CR decreased metastatic burden and therefore may complement cytotoxic therapies being used in the clinical setting for metastatic disease. Downregulation of the IGF-1R pathway, is in part responsible for this response and modulating IGF-1R directly resulted in similar improved progression-free survival. The novel use of CR has the potential to enhance clinical outcomes for patients with metastatic breast cancer.